Temperature management in acute type A aortic dissection treatment: deep vs. moderate hypothermic circulatory arrest. Is colder better? - Abdulwahab, Hend Abdulwahab Muftah; Kolashov, Alish; Haneya, Assad; Klump, Hannes; Moza, Ajay; Arab, Mohamad Fateh; Shoaib, Mohammed; Zayat, Rashad; Khattab, Mohammad Amen (Frontiers in Cardiovascular Medicine, 2024)
Introduction The impact of different degrees of hypothermia in patients undergoing type A aortic dissection (TAAD) repair remains controversial. The purpose of this study was to compare the clinical outcomes of patients who received deep hypothermic circulatory arrest (DHCA) (<20°C) and those of patients who received moderate hypothermic circulatory arrest (MHCA) (20–28°C). Methods Between January 2011 and December 2020, 143 patients underwent surgical treatment for TAAD with CA and unilateral antegrade selective cerebral perfusion (uSCP). In this retrospective analysis, we evaluated the clinical outcomes of 143 individuals (103 who received DHCA vs. 40 who received MHCA). The primary outcome was the composite of major events (CMEs) including delirium, acute kidney injury (AKI), and in-hospital mortality. The secondary outcomes were overall mortality, bleeding, rethoracotomy, and length of intensive care unit (ICU) stay, among other things. Results Compared with the MHCA group, the DHCA group presented a greater incidence of postoperative complications, as follows: AKI (26 (25.2%) vs. 3 (7.5%), p = 0.020), delirium (23 (22.3%) vs. 2 (5%), p = 0.014), re-exploration rate (21 (20.4%) vs. 2 (5.0%), p = 0.024), and prolonged intensive care unit (ICU) stay (7.8 (4.4, 14.1) vs. 5.7 (2.4, 10) days, p = 0.019). The median cardiopulmonary bypass time (255 (210, 280) vs. 210 (190, 251) min, p = 0.010) and median cross-clamp time (140 (110, 180) vs. 125 (100, 160) min, p = 0.023) were significantly longer in the DHCA group. The German Registry for Acute Aortic Dissection Type A (GERAADA) score was significantly higher in the MHCA group (22.7 ± 9.1 vs. 19 ± 7.2, p = 0.012). The adjusted odds ratio for CME in the MHCA group was 0.78 (95% CI: 0.52–1.17, p = 0.001). The use of MHCA demonstrated a protective effect on reducing postoperative delirium (OR: 0.28, 95% CI: 0.14–0.46, p < 0.01) and postoperative AKI (OR: 0.29, 95% CI: 0.14–0.49, p < 0.01). Overall survival after two years did not differ between the two groups (log-rank, p = 0.16). Conclusion The principal findings of our study indicate that DHCA elevates the risk of postoperative AKI and delirium. As a result, the duration of hospitalization and intensive care unit stay was markedly extended. Consequently, MHCA should be favored over DHCA when the clinical circumstances permit, since DHCA remains a secure alternative in intricate dissection instances.